2010
DOI: 10.1111/j.1365-2842.2010.02117.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of surgical technique, implant shape and diameter on the primary stability in cancellous bone

Abstract: Achievement of primary stability during surgical placement of dental implants is one of the most important factors for successful osseointegration depending on various anatomical, surgical and implant-related factors. Resonance frequency analysis (RFA) has been shown as a non-invasive and objective technique for measuring the stability of implants. The aim of this study was to evaluate the effect of some surgical and implant-related factors in enhancing primary stability and to estimate a correlation between R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
84
1
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(101 citation statements)
references
References 35 publications
3
84
1
13
Order By: Relevance
“…Furthermore, relationship between the initial torque and RFA value was observed. Therefore, when smaller drilling was performed than the finally installed implant in the trabecular bone with poor bone quality, placing conical implant secured the primary stability 23. Park et al reported in the experimental study using models that when implant is placed and fixed in cortical bone, ISQ and removal torque value (RTV) were observed to increase; and in the region with poor bone quality, under-drilling can be performed to improve implant stability 24.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, relationship between the initial torque and RFA value was observed. Therefore, when smaller drilling was performed than the finally installed implant in the trabecular bone with poor bone quality, placing conical implant secured the primary stability 23. Park et al reported in the experimental study using models that when implant is placed and fixed in cortical bone, ISQ and removal torque value (RTV) were observed to increase; and in the region with poor bone quality, under-drilling can be performed to improve implant stability 24.…”
Section: Discussionmentioning
confidence: 99%
“…Such stresses may be beneficial for enhancing the primary stability of an implant, but they can reach a sufficiently high level to result in necrosis and local ischemia of the bone at the implant-tissue interface [4-6]. In the same respect, secondary stability can also be determined by the bone tissue response to the surgical trauma and the implant surface.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical modifications such as sub-drilling or the bur diameter in relation to the implant diameter can also affect it (Bilhan et al, 2010). Although sub-drilling can certainly have a positive effect on primary stability in trabecular bones, it must be noted that in uncontrolled conditions it can cause stress on the bone, which although beneficial in the sense of gaining a better primary stability can result in necrosis and local bone ischemia in the bone-implant interface, affecting osseointegration (Nedir et al, 2004).…”
Section: Discussionmentioning
confidence: 99%